AKTIVASI GEN-Z TERHADAP PENGEMBANGAN UMKM MELALUI DIGITALISASI: Studi Kasus di Wilayah Kapanewon Moyudan - Ramdhani, Ahmad Thoriq Akhsan; Agung Rashif Madani (UIN Sunan Kalijaga, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economic growth, contributing significantly to the Gross Domestic Product (GDP) and employment. However, access to financial resources and markets remains a challenge for MSMEs, especially those operating in the Moyudan Subdistrict. This research aims to analyze the role of Generation Z in addressing these challenges through the digitalization of MSMEs. This study is a qualitative descriptive research that involves observations and the collection of primary and secondary data. The research findings reveal that Generation Z plays an innovative role in the development of MSMEs through digitalization. Through digital transformation, MSMEs can enhance their visibility and efficiency through e-commerce platforms and online promotions. This digital transformation is supported by the high internet penetration and social media usage in Indonesia. The government also plays a role in developing digital skills among Generation Z through various programs. Digitally savvy Generation Z individuals can actively contribute to the growth of MSMEs, as seen in the success of the